TEKNIK ROLE PLAYING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI ANTAR PRIBADI SISWA - Putra, Giri Isna; Sutarno, Sutarno; Djannah, Wardatul (Universitas Sebelas Maret, 2013)
This study was a quasi-experimental design with the type of Nonequivalent Control Group Design. The sampling technique was Purposive Random Sampling Technique. Data analysis was using Two-Way ANOVA. Based on the testing result of hypothesis I the value of Fcount is 9,138 and Ftable was 3,92, with the significance level of 0,003<0,05. It is identified that Fcount>Ftable then Ha was accepted. It means that there is significantly difference in the ability of interpersonal communication before being given treatment and after being given treatment. The testing result of hypothesis II the value of Fcount was 5,542 and the Ftable is 3,92, with the significance level of 0,020 <0,05. It was identified that Fcount>Ftable then Ha is accepted. It may imply that there are significantly differences in the ability of interpersonal communications in the experimental group and the control group. The testing result of sub hypothesis III the value of Fcount is 4.850 and the Ftable is 3.92, with the significance level of 0.034<0.05. It is identified that the Fcount > Ftable then Ha is accepted. It means that there is an interaction between groups of interpersonal communication skills on pretest and posttest with interpersonal communication skills in the experimental group and the control group.